Caucasian Relations of the Danubian Basin in the Early Iron Age - Gazdapusztai, Gyula
Horse-Bit Outfits – Caucasian Relations of the Bronze Objects with Openwork Decoration – The Spread of the Kabardian-Piatigorsk Daggers in the West – Caucasian Relations of Some Finds from the Northern Balkans – The Caucasian Relations of the Horizon of the Bîrlad Hoard Find – Elements of Western Origin in the Finds of the Koban Culture.